The influence of domino theories in preventing construction accidents / Muhammad Afiq Rahiman and Noor Aisyah Asyikin Mahat - Rahiman, Muhammad Afiq; Mahat, Noor Aisyah Asyikin (2018)
Accident causation is a complex issue, as there are usually several contributing factors that are the root causes of accidents on sites. There are many available theories on the accident causation, and the most influential theories are the Dominos Theories which has been applied and adapted worldwide until today. Although some causes of accidents are known, the underlying factors that bring about accidents are not yet well understood. This research aims to create proactive measure for accident prevention in Malaysian construction industry. Henceforth, the objectives of the research are to investigate the root cause of accidents and to relate the key elements from the Domino theories that influence the accident causation. This research adopted quantitative approach of research methodology. Fifty (50) sets of questionnaires survey are distributed among the Grade G7 CIDB Registered building contractors. The findings highlight the key factors contributing to accident and the crucial attributes from Dominos Theories that relate to safety precaution in construction environment. Critical contribution factor of accident are identified such as human element, unsafe equipment and the job site condition. Factors preventing from accident also has been identified such as enforcement, training & education, involvement of management and safety awareness and promotion. Strategies on hazard prevention and the awareness of safety in construction could actually spur economy in construction as well as to make construction more productive. Ultimately, it will result in the formulation of preventive health and safety policies that can assist industry to reduce accident occurrence on construction sites.